Corruption accusations and bureaucratic performance: Evidence from Pakistan - Ummad Mazhar; Komal Iftikhar (Economics: The Open-Access, Open-Assessment Journal, 2021)
This study assesses the effectiveness of anti-corruption policies of Pakistan by relating the corruption of government officials to the actual and perceived bureaucratic hurdles faced by formal businesses. It offers a unique perspective by focusing on cases in which the accused officers voluntarily disclosed the misuse of public money (or gains acquired through corruption) in order to avail the option of plea-bargaining. The empirical analysis estimates the effect of these policies on the responses of the managers of business firms in Enterprise Surveys. The number of accusations seems to reduce the incidence of bureaucratic corruption. While the amount that is being offered in bargaining has a negative effect overall, it switches sign overtime suggesting the possibility that it may increase corruption in the long run. The core results are robust across various measures of firm-level corruption. The instrumental variable estimates produce similar results.
Keywords: 330; corruption; Government-business relation; Pakistan; plea bargain; voluntary disclosure